2006
DOI: 10.1002/pros.20444
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride targets prostate vascularity by inducing apoptosis and inhibiting cell adhesion of benign and malignant prostate cells

Abstract: Finasteride can induce prostate apoptosis and reduce tissue vascularity by inhibiting epithelial cell adhesion. This evidence supports that finasteride has apoptotic and anti-angiogenic effects against benign and malignant prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…Moreover, the content of steroid in the culture medium when carrying out the treatment with finasteride can be decisive in the study of apoptotic effect of this compound. On the other hand, and in agreement with our data, several authors have established that finasteride induces apoptotic cell death in prostate tissues of rat (13,28) and men (29,30).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the content of steroid in the culture medium when carrying out the treatment with finasteride can be decisive in the study of apoptotic effect of this compound. On the other hand, and in agreement with our data, several authors have established that finasteride induces apoptotic cell death in prostate tissues of rat (13,28) and men (29,30).…”
Section: Discussionsupporting
confidence: 93%
“…3,4 Previous studies have shown that DHT inhibition cannot persistently and extensively induce apoptosis in prostatic epithelial cells. 5 However, the mechanisms are still largely unknown at present.…”
Section: Introductionmentioning
confidence: 99%
“…7 Finasteride, another 5α-reductase inhibitor, is known to induce apoptosis of the glandular epithelium cells and prostate cancer cells. [8][9][10] Therefore, it is possible that normal capsular structures are destroyed as the structure of the prostate changes, causing inflammation and adhesions. Some BPH patients underwent MRI before and after dutasteride treatment, and findings showed that the surgical capsule was clearly visible before the treatment, and became unclear after 18 months of dutasteride therapy.…”
Section: Discussionmentioning
confidence: 99%